Cellular transformation promotes the incorporation of docosahexaenoic acid into the endolysosome-specific lipid bis(monoacylglycerol)phosphate in breast cancer. (31st March 2023) - Berg, Anastasia L.; Showalter, Megan R.; Kosaisawe, Nont; Hu, Michelle; Stephens, Nathanial C.; Sa, Michael; Heil, Hailey; Castro, Noemi; Chen, Jenny J.; VanderVorst, Kacey; Wheeler, Madelyn R.; Rabow, Zachary; et al.
Abstract: Bis(monoacylglycero)phosphates (BMPs), a class of lipids highly enriched within endolysosomal organelles, are key components of the lysosomal intraluminal vesicles responsible for activating sphingolipid catabolic enzymes. While BMPs are understudied relative to other phospholipids, recent reports associate BMP dysregulation with a variety of pathological states including neurodegenerative diseases and lysosomal storage disorders. Since the dramatic lysosomal remodeling characteristic of cellular transformation could impact BMP abundance and function, we employed untargeted lipidomics approaches to identify and quantify BMP species in several in vitro and in vivo models of breast cancer and comparative non-transformed cells and tissues. We observed lower BMP levels within transformed cells relative to normal cells, and consistent enrichment of docosahexaenoic acid (22:6) fatty acyl chain-containing BMP species in both human- and mouse-derived mammary tumorigenesis models. Our functional analysis points to a working model whereby 22:6 BMPs serve as reactive oxygen species scavengers in tumor cells, protecting lysosomes from oxidant-induced lysosomal membrane permeabilization. Our findings suggest that breast tumor cells might divert polyunsaturated fatty acids into BMP lipids as part of an adaptive response to protect their lysosomes from elevated reactive oxygen species levels, and raise the possibility that BMP-mediated lysosomal protection is a tumor-specific vulnerability that may be exploited therapeutically. Highlights: Bis(monoacylglycero)phosphate (BMP) is an endolysosome-specific phospholipid. Docosahexaenoic acid (DHA, 22:6) in BMP is associated with multiple disease states. Breast tumor cells specifically divert DHA into BMP over other fatty acids. DHA acts as an antioxidant to protect tumor cell lysosomal membranes. Disruption of DHA-BMP accumulation may be an attractive anti-cancer therapeutic strategy.